State estimation based on image processing of chatter mark on end-milled surface by two-dimensional discrete Fourier transform - Nobutoshi OZAKI; Shota MATSUI; Toshiki HIROGAKI; Eiichi AOYAMA (Nihon Kikai Gakkai ronbunshu, 2019)
In this report, we propose a method to analyze the frequency and phase difference of self-excited vibration during cutting by using image analysis for the photographed image of the machined surface by end milling. It is widely known that, when chatter vibration occurs during cutting, periodic patterns, called chatter marks appear on the machined surface. In previous studies, the periodicity of chattering was judged by visual observation, but this reading operation was difficult, and advanced skills were required to obtain stable results. In this study, the periodicity of the chatter mark is analyzed from the frequency spectrum of a two-dimensional discrete Fourier transform. Image analysis of chatter marks by Fourier transform facilitates the evaluation of the periodicity from the entire image data, so it enables very robust frequency analysis compared to conventional methods. The machined surface images necessary for chatter mark analysis were acquired using a commercially available digital camera and machine tool. To verify the effectiveness of the proposed method, chattering vibration generated during side cutting with the end mill was estimated and compared by the image analysis of the chatter mark and vibration analysis with a displacement sensor. The values of both analysis results are close, and it is found that the proposed method is an effective method for chatter vibration analysis.